2010
DOI: 10.1097/jto.0b013e3181da85e4
|View full text |Cite
|
Sign up to set email alerts
|

Why Do Some Lung Cancer Patients Receive No Anticancer Treatment?

Abstract: The proportion of patients with lung cancer receiving no treatment is greater than that predicted by guidelines or recommended by the MDM but lower than that described in population-based studies suggesting that MDMs can improve treatment utilization in lung cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
49
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 31 publications
3
49
0
1
Order By: Relevance
“…These figures varies from 19% in USA, 33% in Australia, 37% in Scotland, and 50% in Ireland and New Zealand (Fry et al, 1999;Vinod et al, 2008;Erridge et al, 2008;Mahmud et al, 2003;Stevens et al, 2007). Vinod et al (2010) have addressed this issue in their study and found that in actual practice 20% patients didn't receive any treatment; however guideline recommendations for no treatment were there in only 4% patients. On multivariate analysis, it was observed that main factors responsible for this discrepancy were older age, poor PS, NSCLC histology and social reasons.…”
Section: Discussionmentioning
confidence: 99%
“…These figures varies from 19% in USA, 33% in Australia, 37% in Scotland, and 50% in Ireland and New Zealand (Fry et al, 1999;Vinod et al, 2008;Erridge et al, 2008;Mahmud et al, 2003;Stevens et al, 2007). Vinod et al (2010) have addressed this issue in their study and found that in actual practice 20% patients didn't receive any treatment; however guideline recommendations for no treatment were there in only 4% patients. On multivariate analysis, it was observed that main factors responsible for this discrepancy were older age, poor PS, NSCLC histology and social reasons.…”
Section: Discussionmentioning
confidence: 99%
“…Despite advances in anticancer therapies, survival benefits in patients with lung cancer over the past 30 years have been relatively small compared with those seen in breast, colorectal and prostate cancers 22. While reasons for this are complex, many patients with lung cancer are ineligible for radical treatment at presentation due to poor PS or comorbidity, while others fail to receive their intended treatment plan because of functional decline 23 24. Non-small cell lung cancer (NSCLC) has a particularly strong association with loss of muscle mass—of 441 patients consecutively referred to a regional oncology service, 47% were found to be sarcopenic 25.…”
Section: Introductionmentioning
confidence: 99%
“…It has been recently shown that multidisciplinary cancer care and meetings enhance the adherence to guideline-and evidence-based care in NSCLC. 19,20 The stage at diagnosis was the only factor shown to correlate with the treatment guideline adherence rate in our cohort, with patients with advanced (stage IV) NSCLC having a higher rate of nonadherence to treatment guidelines. The most common practice that deviated from evidence-based care was the use of cytotoxic chemotherapies of unproven value as a third-line regimen in patients with stage IV NSCLC.…”
Section: Discussionmentioning
confidence: 80%